The Applicability of ADA, AFU, and LAC in the Early Diagnosis and Disease Risk Assessment of Hepatitis B-Associated Liver Cirrhosis and Hepatocellular Carcinoma - Zhang, Wei; Chen, Zhong; Xue, Chengjun; Zhang, Yao; Wu, Lipei; Zhu, Jichao; Xuan, Shihai; Tian, Jiale; Pang, Zhi (Frontiers in Medicine, 2021)
Objective: To evaluate the applicability of adenosine deaminase (ADA), ɑ-L-fucosidase (AFU), lactic acid (LAC), and their combined detection in the early diagnosis of chronic hepatitis B (CHB), liver cirrhosis (LC), and hepatocellular carcinoma (HCC) Methods: A retrospective analysis of hepatitis B-positive liver disease patients admitted between 2015 and 2020 was conducted. The receiver operating characteristic (ROC) curve was used to determine the diagnostic value of each indicator in LC and HCC, and binary logistic regression analysis was performed to determine the factors and risks related to the occurrence of the two conditions. Results: The levels of ADA, AFU, and LAC were significantly increased in patients with CHB, LC, and HCC (P<0.05). The ROC curve showed that the sensitivity and specificity of ADA, AFU, LAC, and their combined detection in the CHB and LC groups as well as in the LC and HCC groups reflected different degrees of clinical value. In the CHB and LC groups, the adjusted odds ratio (OR) values of ADA, AFU, and LAC among patients in the high-level group were 3.218, 1.859, and 11.474, respectively when the median was considered the cut-off point. When quartiles were considered the cut-off point, the or risk values of the adjusted levels of ADA, AFU, and LAC were higher than those of the lowest level group (Q1) (P<0.05). In the LC and HCC groups, the adjusted OR values of ADA, AFU, and LAC among patients in the high-level group were 0.967, 2.365, and 38.368, respectively. When quartiles were considered the cut-off point, the or risk values of AFU and LAC levels were higher than those of the lowest level group (Q1) (P<0.05). Conclusion: ADA, AFU, and LAC demonstrated good value in the early diagnosis of LC and HCC. The combined detection of ADA+AFU+LAC is more effective than single detection for the early diagnosis of the two conditions. ADA, AFU, and LAC can serve as risk predictors of LC, while AFU and LAC can be considered early risk predictors of HCC.